Trakai Castle Court Acts of 1660–1661 from the Vilnius University Library Сollection. II - Ušinskienė, Viktorija (Slavistica Vilnensis, 2015)
The article was prepared as part of the research project Court Books of the Grand Duchy of Lithuania (GDL): A Digital Database, undertaken by the Vilnius University Library in 2011–2014 (VUL, Nr. LIT-5-19). The paper deals with the hitherto unstudied Trakai Castle Court Acts of 1660–1661 (F7-MDGs, 1660–1661) from the VUL collection, and presents Part II of the critical catalogue of manuscripts written in Polish and Ruthenian languages, as well as their descriptions (leaves 210–466). These documents are important for the study of Lithuanian, Polish and Belarusian history, as their contents reflect a broad political, social and cultural panorama of the multilingual GDL society. This feature of the manuscripts enables us to consider them as unique reference books that represent the changing sociolinguistic situation in the GDL.